«Սոցիոլոգիա» մասնագիտությամբ ուսանողական ինքնուրույն գիտական աշխատանք գրելու հմտություններ - Մխիթարյան, Սամսոն (Զանգակ հրատ.)
В статье обосновывается необходимость обучения студентов навыкам написания самостоятельных научных работ. На примере написания дипломных исследований предлагается ряд учебно-методических подходов к работе с материалами, структурированию работы, обоснованию выдвигаемых тезисов и презентации студентами своего научного исследования. The article discusses the need in transferring skills of writing academic papers which are very useful while students prepare their course and diploma works. As a part of academic writing, the author proposes methodological approaches to teaching students how to write diploma works, including collection of materials, structuring of the text and argumentation of the theses, as well as representing the work for defense.
Keywords: Ուսուցման և դասավանդման մեթոդիկա